How to be a good wife - Chapman, Emma, 1985- (St. Martin's Press, 2013)
Marta's husband "has always taken care of her, and she has always done everything she can to be a good wife--as advised by a dog-eared manual given to her by Hector's aloof mother on their wedding day. But now, something is changing. Small things seem off. A flash of movement in the corner of her eye, elapsed moments that she can't recall. Visions of a blonde girl in the darkness that only Marta can see. Perhaps she is starting to remember--or perhaps her mind is playing tricks on her. As Marta's visions persist and her reality grows more disjointed, it's unclear if the danger lies in the world around her, or in Marta herself"--